Patch atlas : integrating design practices and ecological knowledge for cities as complex systems - Marshall, Victoria J. (Victoria Jane); Cadenasso, Mary L.; McGrath, Brian; Pickett, Steward T., 1950- (Yale University Press, 2019)
A new tool for mapping urban land cover that integrates design principles and ecological knowledge for understanding cities as complex, patchy and dynamic systems Using a new, hybrid approach to urban land cover classification as an impetus to bring ecologists and urban designers together, this atlas is a unique conceptual tool to describe and analyze cities as complex systems. It brings together over a decade of shared knowledge from the Baltimore Ecosystem Study to inspire ecologically motivated design practice. The atlas displays maps and tables depicting land cover classes and the relationships between them; information on how the specific cover arrangements evolved over time; and speculations on how they might change through design, disturbance, or succession. Rather than separating human-constructed spaces from predominantly biological and geological ones, this book integrates social and ecological structures and shows how this can contribute to the scholarship of ecology and the practice of design. Interdisciplinary and strikingly illustrated, the atlas is a new way to study, measure, and view cities with a more effective interaction of scientific understanding and design practice.